Determination of the shear traction-separation law of adhesive layers using the end-notched flexure specimen. (August 2020) - de Morais, A.B.
Highlights: A method is proposed to determine the bondline shear traction-separation law. It only requires common load-displacement data of end-notched flexure tests. It is easily implemented with an approximate tetra-linear traction-separation law. The base beam cohesive zone model was validated by finite element analyses. Application to some published experimental results showed considerable potential. Abstract: Cohesive zone modelling is increasingly applied to predict the strength of structural adhesive joints. A method is here proposed to determine the bondline shear traction-separation law needed for cohesive zone models. The method combines an effective crack length approach derived from a beam model and an existing J -integral analysis of the end-notched flexure specimen. The resulting work done by the tractions versus separation curves can be easily processed with direct or mixed direct-inverse approaches. Application to some published experimental results demonstrates the potential of the method while highlighting the importance of adherend material and specimen geometry selection.